Correlation between gut microbiota dysbiosis and colorectal cancer: review - Chilimoniuk, Zuzanna; Dudziński, Dominik; Borkowska, Aleksandra; Chałupnik, Aleksandra; Więsyk, Piotr; Chilimoniuk, Beata; Gawłowicz, Łukasz; Grzegorzak, Filip; Stasiak, Katarzyna (Quality in Sport, 2024)
Introduction and Purpose: The human gut microbiota, comprising a diverse consortium of approximately 100 trillion microorganisms, is integral to maintaining health and modulating disease processes. Its development begins at birth, influenced by maternal microbiota and environmental factors. Dysbiosis, defined as an imbalance in the gut microbial composition, has been implicated in a range of gastrointestinal pathologies, including colorectal cancer (CRC). This review endeavors to elucidate the relationship between gut microbiota and CRC, examining the impact of specific bacterial taxa on the pathogenesis CRC. Description of the State of Knowledge: Gut microbiota encompasses a multitude of microbial species, with their composition differing along the gastrointestinal tract. Healthy gut microbiota perform essential functions such as pathogen protection, metabolic processes, and immune system modulation. Factors like diet and genetics significantly influence microbial composition. Dysbiosis contributes to CRC through inflammation, genotoxin production, and immune modulation. Specific bacteria, such as Fusobacterium nucleatum and Bacteroides fragilis, are associated with CRC. Mechanisms of carcinogenesis include bacterial adherence, invasion of epithelial cells, and activation of pro-inflammatory pathways. Summary: Understanding the gut microbiota's role in CRC highlights the importance of maintaining a balanced microbiome for cancer prevention. Dietary interventions promoting beneficial bacteria and reducing harmful species could mitigate CRC risk. Further research should prioritize the identification of microbial biomarkers for early CRC detection and the development of therapeutic strategies aimed at modulating the gut microbiota. These efforts will enhance CRC prevention and treatment modalities.